2017
DOI: 10.1017/s0950268817001388
|View full text |Cite
|
Sign up to set email alerts
|

Pork products associated with human infection caused by an emerging phylotype of hepatitis E virus in England and Wales

Abstract: Since 2010, human hepatitis E infections have increased in England and Wales. Most cases are locally acquired and caused by hepatitis E virus genotype 3 (HEV G3). HEV G3 is linked to the consumption of pork products. The increase is associated with the emergence of a new phylotype, HEV G3-group 2 (G3-2, also known as G3abcdhij). Sixty individuals with confirmed hepatitis E infection and no history of travel outside the UK were recruited: 19 were infected with HEV G3-group 1 (G3-1 or G3efg) and 41 with G3-2. Ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 15 publications
2
30
0
Order By: Relevance
“…However, while the genotype of HEV circulating in people in the UK is HEV G3 subgroup 2, HEV in British pigs is mainly HEV G3 subgroup 1 (Ijaz et al, ). Thus, most human infections in the UK appear to be either from imported pork products (Said et al, ; Salines, Andraud, & Rose, ) or there may be an alternative zoonotic source such as peri‐domestic wildlife.…”
Section: Introductionmentioning
confidence: 99%
“…However, while the genotype of HEV circulating in people in the UK is HEV G3 subgroup 2, HEV in British pigs is mainly HEV G3 subgroup 1 (Ijaz et al, ). Thus, most human infections in the UK appear to be either from imported pork products (Said et al, ; Salines, Andraud, & Rose, ) or there may be an alternative zoonotic source such as peri‐domestic wildlife.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, studies have shown that 5.7% of UK (10), and 44.4% of Scotland (11) slaughterhouse market-weight pigs were viremic. A growing number of reported cases of autochthonous HEV-3 and HEV-4 human infection have been attributed to consumption of raw or undercooked pork (12,13), including 1 case acquired from imported HEV-4 in the United States (14). The HEV sequences we detected all belonged to the zoonotic HEV-3 group 2 (HEV-3abchij).…”
Section: Discussionmentioning
confidence: 76%
“…Because our phylogenetic analysis was based on partial sequences, our results identified the prevalent HEV genotype at the group level, but more detailed study based on fulllength sequence is warranted to definitively identify viral heterogeneity as well as the molecular clock of HEV evolution across the United States. Cases of autochthonous human infection with HEV-3abchij have been reported in the United Kingdom (13), and low levels of HEV-3abchij RNA were detected in human blood donor plasma samples in the United States (4). That ≈6% of slaughterhouse pigs are still viremic for HEV-3abchij raises a potential concern about pork safety because blood containing infectious HEV during slaughter may contaminate raw pork products.…”
Section: Discussionmentioning
confidence: 99%
“…25 Increasing efforts in HEV surveillance has revealed a complex picture of the global circulation of HEV-3 subtypes, with no clear regional demarcations. Subtypes are no longer limited to their regions of origin, such as the discovery of both major HEV-3 groups in UK even though only G3efg has been found in indigenous pigs, 26 as well as the discovery of HEV-3f viruses in Bangkok retail pork in supermarkets. 27 All of the National University Hospital (NUH, Singapore) sequences in this study fall within subtype 3a on the phylogenetic tree.…”
Section: Discussionmentioning
confidence: 99%